DISTANCE EDUCATION: a possible contribution to cooperative education - Frare, Jian Carlos (2022)
This article presents a reflection on the possible contributions of Distance Education in the framework of pedagogical practices developed in cooperative organizations. The discussion starts from the need to think about the education (formation and training) of associates from a movement of liberation of the subject, through critical consciousness, based on the principles and values of cooperativism. From this, we discussed the importance of Distance Education actions as a way to strengthen values and principles of cooperativism and the participation of co-operatives in the discussions of cooperatives, contributing so that organizations do not become just instruments of reproduction of the individualism in the capitalist perspective.